Study on Structure and Remaining Oil Distribution Characteristics in Area 12 of Weigang - Liyan Sun, Zhiyuan Guo, Jicheng Zhang, Jia Niu (Forest Chemicals Review, 1970)
Through research, the occurrence and distribution law of faults are determined, the causes of complex fault block groups and the distribution characteristics of remaining oil are studied, and the development effect of complex fault block reservoirs is improved. The geological conditions of Weigang Oilfield, especially the characteristics of fault structures, are extremely complex. Determine the types and combination styles of faults, restore micro-geological structures as accurately as possible, and clarify the distribution of underground surplus resources.